1986
DOI: 10.1111/j.1528-1157.1986.tb03512.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Blind, Placebo‐Controlled Study of Vigabatrin (Gamma‐Vinyl GABA) in Drug‐Resistant Epilepsy

Abstract: Vigabatrin (GVG) (3 g/day) and placebo were compared as an add-on to standard therapy in therapy-resistant epileptic patients using a double-blind crossover design with randomized treatment allocation. Twenty-three patients entered the trial, with four dropping out due to either increased seizure frequency following the cross-over from GVG to placebo (n = 1), intolerance to GVG therapy (n = 2), or poor seizure record (n = 1). Of the 19 patients who completed the study, 17 had partial seizures, eight of whom ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 19 publications
5
67
1
Order By: Relevance
“…Vigabatrin (-y-vinyl GABA), a specific, enzymeactivated irreversible inhibitor of GABA-transaminase (GABA-T) has been shown to be an effective anti-convulsant agent for complex partial seizures (Gram et al, 1983;Browne et al, 1983;Rimmer & Richens, 1984;Gram et al, 1985;Loiseau et al, 1986;Schechter, 1986;Tartara et al, 1986;Tassinari et al, 1987). In all published studies to date vigabatrin has been administered orally on a twice-daily schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Vigabatrin (-y-vinyl GABA), a specific, enzymeactivated irreversible inhibitor of GABA-transaminase (GABA-T) has been shown to be an effective anti-convulsant agent for complex partial seizures (Gram et al, 1983;Browne et al, 1983;Rimmer & Richens, 1984;Gram et al, 1985;Loiseau et al, 1986;Schechter, 1986;Tartara et al, 1986;Tassinari et al, 1987). In all published studies to date vigabatrin has been administered orally on a twice-daily schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Vigabatrin (-y-vinyl GABA) is a new antiepileptic drug, recently demonstrated to have a consistent anticonvulsant effect in double-blind placebo-controlled trials of patients with chronic drug-resistant epilepsy (Rimmer & Richens, 1984;Gram et al, 1985, Loiseau et al, 1986Tartara et al, 1986). The postulated mechanism of action of vigabatrin in epilepsy is believed to be irreversible or 'suicide' inhibition of the cerebral enzyme, GABA-aminotransferase (GABA-T), resulting in elevated brain concentrations of the inhibitory neurotransmitter, -yaminobutyric acid (GABA) .…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated in an adjunctive crossover study in which seizures worsened in some patients crossing over from VGB to placebo but not in those changing from placebo to VGB (20)(21)(22). A withdrawal rate of 0.5-1 @week is usually safe.…”
Section: Effect Of Age and Disease Statementioning
confidence: 99%
“…In most studies, responder (50% seizure reduction) rates were between 40 and 50%, as were mean overall seizure reduction rates. All controlled trials have shown statistically significant seizure reductions in VGB treated patients (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Efficacymentioning
confidence: 99%